Transformational Chair Design Analogous To Malaysia’s Rafflesia Plant Cellular Structure - Fu, Chew Xiang; Muslim, Zulkifli (2014)
The purpose of this paper is to provide a review of literature on Rafflesia cellular structure endemic to Malaysia Identity that is suitable to be applied in chair transformation design process which can help individual developing their understanding in plant analogy design. It is a critical and comprehensive review of a range of recently published literature sources (until May 2014) addressing various issues related to the transformation process design theory, Rafflesia Azlanii, and chair design. The sources are sorted into sections: morphological identification of Rafflesia, design for transformation and the analogy between R.A and chair. The paper provides insights about the characteristic and growth principle of R.A structure and form endemic to Malaysia resources; transformation process design theory that may influence the analogy between R.A cellular structure and chair design as a Malaysia identity product; and its benefits and guidelines to students/educators/designers of using R.A cellular structure as an analogy in developing chair design. It is hoped that the analysis, as captured in this paper, will highlight the different transformation process design theory in chair development. The paper will be of interest to researchers in the areas of tropical plant analogy design, enable learning environments, in general. Further, this paper demonstrates how the analysis of academic literature sources has been combined with commentaries and opinions on the journals and articles to develop this literature review. The finding is a very useful source of information and impartial advice which may be commercialized and influence learning and teaching strategies in higher and further education – specifically institutions that are considering the use of R.A cellular structure in chair design. This paper fulfils an identified information/resources of transformation design theory, design analogy of R.A cellular structure in chair design needs and offers practical help to students/educators/designers starting out a plant structure analogy design direction.